ANALISIS PENGGUNAAN METODE PERMAINAN KARTU PADA SISWA KELAS X AKUNTANSI SMK NEGERI 8 PONTIANAK - Dewinda Chintya Nafisa Pratikno; Ina Ina; Suhardi Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract Game method is a method that uses the game to carry out teaching. In the teaching process, a game full of passion and challenges. Games also provide much ease in th eteaching process. In a pleasant classroom atmosphere, students will more quickly understand the contents of the teaching. The purpose of research is to understand whether using game methods can improve student’s memory and mastery of the Mandarin vocabulary. The author using game method on research in SMK NEGERI 8 Pontianak grade 10th accounting class.The result is that using a game method can improve student’s memories of the chinese vocabulary, besides that it can also improve student test score. Student final test scores are higher than previous test score. Test scoreon grade 10th accounting class number 1 increased 33% while on grade 10th acconting class number 2 increased 29%. We can conclude that use game method in teaching process can help to improve student’s ability in memorize Mandarin’s vocabularies.Keyword: Vocabularies Vocabulary Teaching Game Teaching Method